Confidence Intervals for State Price Densities - Zdeněk Hlávka (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 2003)
The state price density is a second derivative of the discounted European options prices with respect to the strike price. We use Maximum Likelihood method to derive a simple estimator of the curve such that it is decreasing, convex and its second derivative integrates to one. Confidence intervals for this estimator can be constructed using standard Maximum Likelihood theory. The method works well in praxis as illustrated on the DAX option prices data.
urn:nbn:de:kobv:11-10050408
Keywords: 330; option pricing; state price density estimation; nonlinear least squares; confidence intervals; Optionspreistheorie; Maximum-Likelihood-Methode; Schätztheorie; Nichtlineares Verfahren; Schätzung; Index-Futures; Theorie; Deutschland